GAMBARAN PENGETAHUAN IBU TENTANG PENCEGAHAN STUNTING PADA ANAK BALITA - Siagian, Regina; Firman Sekozen Sihombing; Ripandi Siregar; Haryanti Sibuea; Khairun Nisa Putri; Muhammad Naufal Arif Lubis; Regina Oktavia (Citra Internasional Institute, 2024)
Stunting is one of the major health problems that has been the focus of the Indonesian government's health development programme for the period 2015-2019, in addition to the reduction in maternal and infant mortality rates, as well as the control of infectious and non-communicable diseases. Stunting is a chronic malnutrition condition that a child experiences from the womb to early growth, resulting in a child's height falling below the age standard. The aim of this study is to find out what mother knows about stunting prevention in young children in the city field. The design of the study uses a descriptive method with a cross sectional approach with a sample of as many as 30 respondents. The analysis was done by spreading the questionnaire given to the mother who had a baby. The results of this study showed that the knowledge of stunting prevention respondents Good is 28 people (93.3%), knowledge Less as much (6.7%) or as much as 2 respondents, and on knowledge of respondents classification Quite none (0%).